Hipertensión arterial crónica no controlada y disfuncionalidad familiar, en el hospital de Jerusalén del distrito La Esperanza – Trujillo - Serván Díaz, Romina Fernanda (2019)
The present work aims to determine the relationship between Chronic Uncontrolled Arterial Hypertension and family dysfunction. through a correlational study that will focus first of all on the value of the family, its functionality and dysfunctionality in the social field of health, being fundamental to emphasize the Family APGAR (Smilkstein, 1978) as an instrument for Primary Care due to its approach to the analysis of family function based on the premise that family members perceive the functioning of the family and can express the degree of satisfaction according to the fulfillment of its basic parameters. Then, we will proceed to cite the main studies that weigh the problems of Arterial Hypertension associated with issues of a family nature for; finally, to establish the degrees of relationship between these two variables.